2018
DOI: 10.1111/ijd.14262
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous lymphoma in Argentina: a report of a nationwide study of 416 patients

Abstract: Background The aim of this study was to determine the relative frequency of primary cutaneous lymphoma (PCL) in Argentina according to the new World Health Organization (WHO)-European Organization for the Research and Treatment of Cancer (EORTC) classification system.Methods A total of 416 patients from 21 dermatology services were included during a 5-year period (2010-2015); these patients were classified using WHO-EORTC criteria.Results There were 231 (55.2%) males and 185 (44.8%) females; the male-to-female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
2
8
1
3
Order By: Relevance
“…BioMed Research International reported worldwide [3-6, 8-10, 14-16]. This finding is consistent with those reported in studies from China (94.5%) [10], Iran (96%) [17], Argentina (93%) [16], and Taiwan (92.3%) [18], but relatively higher than those from Japan (85.7%) [8] and Korea (88%) [9]. Our study emphasizes that non-Caucasian populations appeared to have a higher proportion of CTCLs than those of Caucasian populations (USA, 72.4% [6]; Netherlands and Austria, 78% [4]; Germany, 85% [5]; Switzerland, 72% [15]; Italy, 78.7% [3]).…”
Section: Discussionsupporting
confidence: 89%
“…BioMed Research International reported worldwide [3-6, 8-10, 14-16]. This finding is consistent with those reported in studies from China (94.5%) [10], Iran (96%) [17], Argentina (93%) [16], and Taiwan (92.3%) [18], but relatively higher than those from Japan (85.7%) [8] and Korea (88%) [9]. Our study emphasizes that non-Caucasian populations appeared to have a higher proportion of CTCLs than those of Caucasian populations (USA, 72.4% [6]; Netherlands and Austria, 78% [4]; Germany, 85% [5]; Switzerland, 72% [15]; Italy, 78.7% [3]).…”
Section: Discussionsupporting
confidence: 89%
“…In two studies from Korea, the percentage of FMF in all MF patients accounted for around 2% and 4% respectively 19,20 . In a study in Argentina 21 , the portion was about 6%.…”
Section: Discussionmentioning
confidence: 94%
“…In total, 16,953 patients from 26 different studies were enrolled in the present meta-analysis. The majority of the studies were reported in European populations; only one South American cohort [ 7 ] met the inclusion criteria, and none from Australia or Africa did. The publication dates were evenly distributed over two decades, however there was a gap between 2014 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…A mutational profile consistent with ultraviolet B exposure has been identified in CTCL [ 6 ], but a causal role of ultraviolet exposure in the occurrence of CTCL has not yet been demonstrated. Several epidemiological studies have been reported [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], but no worldwide meta-analysis has been published to date.…”
Section: Introductionmentioning
confidence: 99%